Pemanfaatan Limbah Padat Ternak Sebagai Pupuk Kandang Pada Tanaman Cabai Merah (Capsicum annum L.) - S. Kusuma, Rendy; Sariyyah, Naila; Azzikra, Ardhi; S. Manurung, Joyce; N. Sigalingging, Enjel; O. L. Amukti, Crussel; C. Agustina, Audisti; Anggraini, Dita; Tribuana Tunggadewi, Andini (BULLET : Jurnal Multidisiplin Ilmu, 2024)
Livestock waste is the remaining waste from livestock business activities, such as livestock raising businesses, slaughterhouses, processing of livestock products, etc. Livestock waste generally includes all manure produced from livestock business activities, whether in the form of solid waste such as feces, liquid waste in the form of urine, gas waste in the form of CH4 methane gas, leftover feed, biogas, and organic waste. The total waste produced by livestock depends on the livestock species, the size of the livestock business, the type of business and the floor of the pen. This research aims to utilize livestock waste as raw material for making manure, which is a useful solution to support the agricultural and plantation sectors and minimize environmental pollution. It is hoped that fertilization can play a dual role, apart from providing nutrients, the added fertilizer can also reduce the toxicity of pollutants (Sudirja et al. 2023). This testing stage includes the process of making fertilizer and testing the fertilizer. In the process of making fertilizer using solid waste cow and goat manure taken from the livestock pens of the IPB University Vocational School.  Then, fertilizer testing was carried out by looking at the growth of red chili plants as a parameter for the success of the fertilizer. Based on the experiments that had been carried out, each replication produced mature manure with the characteristic black color, loose texture, odorless and at room temperature. Providing a mixture of cow and goat fertilizer to chili plants resulted in varying growth rate values ​​from the beginning of the fertilizer test, namely week zero, to the end of the test in the third week. This is due to differences in the adaptability of plants to environmental conditions.